General Considerations on Compaction of Specimens of Hot Mix Asphalt (HMA) in the Superpave® Gyratory Compactor - Jiménez Acuña, Mónica (2012)
The compaction of hot mix asphalt (HMA) in the Superpave® Gyratory Compactor is the developments in the laboratory mixture design. The compaction equipment was designed in order to simulate the densification that occurs on site during construction and in service. Another objective was to measure somehow the “workability” of the mix, said it in other words, how easy or difficult is to compact the asphalt mixture. Also, it was considered the use of larger size aggregates. Finally, the equipment should be easy enough to use in conducting the quality assurance and control tests. This article summarizes the history, the operation of the equipment, the test method, the results and finally, the conclusions and recommendations based on the experience gathered over the years using this equipment in LanammeUCR.